A real options perspective on sequential acquisitions in China - Xu, Dean; Zhou, Changhui; Phan, Phillip H (Journal of International Business Studies, 2010)
We examine how firms in an emerging market address their information disadvantage in takeovers. One strategy is to complete the acquisition sequentially rather than as a one-time deal. In contrast to firms in developed economies that enjoy relatively easy access to information, emerging-market firms face differential access to information on target firms, owing to institutional weaknesses and constraints in those markets. Sequential acquisitions are conceptualized as a real-option-based strategy, whereby the sequential acquirer resolves valuation uncertainty through information gathering and learning after making a toehold purchase. The value of a sequential acquisition strategy increases for firms that are at an information disadvantage. Statistical analysis, based on 272 completed acquisitions of Chinese listed firms between 1995 and 2003, shows that the sequential method is more likely to be chosen over a single-transaction mode when the acquirer is a private firm, or when the acquirer is diversifying into a new business area. Thus we offer a new way of viewing real option strategies in emerging economies, by treating sequential acquisitions as information and learning mechanisms as opposed to tools for hedging.